2007
DOI: 10.1016/j.ejvs.2006.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Fenestrated and Branched Stent-grafting After Previous Surgery Provides a Good Alternative to Open Redo Surgery

Abstract: Our report highlights the potential of fenestrated and branched technology to improve re-operative aortic surgical outcomes. The unique difficulties of increased graft on graft friction hindering placement, short working distance, and increased patient co-morbidities should be recognized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0
5

Year Published

2009
2009
2013
2013

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(40 citation statements)
references
References 16 publications
0
35
0
5
Order By: Relevance
“…Previous reports from our institution and others 1,[3][4][5]17 have demonstrated that primary aneurysms involving the visceral segment of the aorta can successfully be managed with totally endovascular procedures with good outcomes. Because both our short and long-term results have been excellent with this method of repair, we prefer to repair all juxtarenal aneurysms by endovascular means, even in good operative risk patients.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Previous reports from our institution and others 1,[3][4][5]17 have demonstrated that primary aneurysms involving the visceral segment of the aorta can successfully be managed with totally endovascular procedures with good outcomes. Because both our short and long-term results have been excellent with this method of repair, we prefer to repair all juxtarenal aneurysms by endovascular means, even in good operative risk patients.…”
Section: Discussionmentioning
confidence: 88%
“…The technique for endograft deployment has been described in detail previously. 2,4,6,7 Briefly, open femoral artery exposure was performed on one or both sides depending on the number of fenestrations and type of visceral revascularization planned. Axillary artery cut-down was used when a caudally-oriented directional graft branch was used for branch vessel revascularization.…”
Section: Subjects and Databasementioning
confidence: 99%
See 2 more Smart Citations
“…Modular grafts are extended from an area of normal-caliber aorta in the descending thoracic aorta to a landing zone distally in either the infrarenal aorta or the bilateral iliac arteries. When there is arch involvement, it often [38] 1 1 3 2 7 Button and Jenkins [39] 1 5 0 0 Verhoeven et al [36] 3 0 2 7 [42] 90.7 19 Muhs et al [40] 9 2 4 6 Ziegler et al [43] 92.2 72 Scurr et al [44] 96.6 24 Kristmundsson et al [45] 9 6 2 5 is necessary to first perform open arch replacement using the elephant trunk procedure to provide an area in the proximal descending aorta of suitable caliber to provide a landing zone for the stent graft. Once the graft is deployed, branch vessels are cannulated through it (either through the fenestrations or the branches) and combined with small balloon-expandable covered stents to accommodate visceral arteries.…”
Section: The Proceduresmentioning
confidence: 97%